Exploring Early Childhood Development Practitioners’ Perceptions of the Implementation of Norms and Standards in Educare Centres in Blouberg - Ross, Jetara (Department of Social Development, 2020)
This study explores the perceptions, experiences and challenges that Early Childhood Development (ECD) practitioners in ECD centres in Blouberg have with implementing the norms and standards for both partial care facilities and learning programmes as regulated by the Children’s Amendment Act 41 of 2007. ECD refers to the developmental, physical, mental, spiritual, emotional and social processes in children from birth until at least nine years of age (Department of Education [DOE], 2001). Since ECD centres are at the frontline of providing a range of ECD services paramount to the development of children, the way in which ECD practitioners understand, experience and operate under the influence of legislation and policies needs to be researched to improve service delivery and develop effective models of practice. The study targeted ECD centres in the Blouberg region of the Western Cape where 20 ECD practitioners belonging to 18 ECD centres were interviewed. An exploratory qualitative research design and a non-probability sampling approach making use of both purposive and snowball sampling techniques, were used to select the participants. The main findings emanating from the study were that: most ECD practitioners perceived that the norms and standards for ECD facilities promote the safety and protection of their service recipients; the implementation of norms and standards, however, were not effectively monitored; they were extremely costly to implement; practitioners did not have sufficient time in the day to implement them; that adhering to norms and standards for ECD learning programmes enhanced the development of the child and cultivated diversity; continuous changes in the curriculum posed various challenges to how effective learning programmes were monitored; norms and standards for learning programmes did not adequately account for children with disabilities; factors such as the long and difficult registration and re-registration processes, as well as the local economy and external financial environment made implementing norms and standards challenging; ECD practitioners in smaller, privately run centres experienced a lack of support from government; and that ECD practitioners were supported by various structures such as the Blouberg ECD Forum, the Department of Health, the Fire and Rescue Services as well as the local community that consisted of parents, businesses and professionals. The main recommendations emanating from the study include: providing tax incentives to private sectors supporting ECD centres; increasing the capacity, responsibility and authority of local ECD Forums; improving the Department of Social Development’s (DSD) reporting and investigating processes by partnering with the Department of Health (DOH), extending the current national school feeding scheme to include ECD centres; providing a once off registration/re-registration grant to NPO’s and smaller privately run ECD centres based on a means test; increasing support and introducing an increased grant to ECD centres catering for children with disabilities; promoting partnerships with professionals in the private sector to promote disability screening campaigns and education; to provide ECD centres with specific curricula so that they are able to cater for children with disabilities; rewarding positive parent-practitioner partnerships; and promoting parent involvement practices from a policy and legislation point of view. Recommendations relating to the research process specifically include expanding on the sample of participants to include privately run ECD centres as well as NPO’s.